Combination of CD160 and CD200 as a useful tool for differential diagnosis between chronic lymphocytic leukemia and other mature B‐cell neoplasms. (3rd December 2014) - Lesesve, J.‐F.; Tardy, S.; Frotscher, B.; Latger‐Cannard, V.; Feugier, P.; De Carvalho Bittencourt, M.
Summary Introduction Chronic lymphocytic leukemia is usually diagnosed through the characteristic morphology/immunophenotype of the lymphocytes, but some CLL cases remain atypical resulting in diagnostic uncertainty. Methods Using flow cytometry analysis, we investigated the expression of CDs160/200 on B cells from 124 patients (82 CLL, 42 other B‐cell neoplasms) and nine controls. CDs160/200 measurements were determined as a ratio of the mean fluorescence intensities of leukemic cells/controls and were considered positive when the ratios were ≥2 and 20, respectively. Results Sixty and 83% CLL expressed CDs160/200 as compared to 5% and 10% of other B‐cell neoplasms, respectively. None of the controls showed CDs160/200 expressions. Combination of both markers was observed in 55% of CLL but only in 2% of other B‐cell neoplasms, and absence of both markers occurred in 12% of CLL but in 86% of other B‐cell neoplasms. Conclusion CDs160/200 were associated with markers of the gold standard 'Matutes score' and could be useful markers to differentiate atypical CLL from other B‐cell neoplasms in the absence of available biopsies or cytogenetics and molecular studies.